Nauczanie religii w kontekście reformy systemu edukacji - Zellma, Anna (Studia Pastoralne, 2026)
Current changes in the Polish education system give rise to new challenges as well as to teaching and educational dilemmas. They also affect religious education in schools, necessitating discussions and catechetical analyses. This paper focuses on the need to develop new core curriculum for religious education, as well as new syllabuses, textbooks and teaching aids for religious instruction in kindergartens, primary and secondary schools. It indicates the need to specify the stage of school education at which students should be prepared for First Confession and First Holy Communion and for the Sacrament of Confirmation. It is considered important to support teachers of religion in developing competence required to undertake tasks resulting from the reform of the education system. The challenges identified in this way require in-depth and multifaceted reflection and discussion, involvement of competent catechists and religious instructors in solving dilemmas and designing innovative didactic and educational solutions. Teamwork directed towards supporting children and youth in their integral development and education in faith, enhanced with interdisciplinary correlation, can result in bringing forward valuable proposals for religious education in schools.